Copyright and cultural institutions : guidelines for digitization for U.S. libraries, archives, and museum / Peter B Hirtle, Emily Hudson, Andrew T Kenyon - Hirtle, Peter B
The development of new digital technologies has led to fundamental changes in the ways that cultural institutions fulfill their public missions of access, preservation, research, and education. Many institutions are developing publicly accessible Web sites that allow users to visit online exhibitions, search collection databases, access images of collection items, and in some cases create their own digital content. Digitization, however, also raises the possibility of copyright infringement. It is imperative that staff in libraries, archives, and museums understand fundamental copyright principles and how institutional procedures can be affected by the law. "Copyright and Cultural Institutions" was written to assist understanding and compliance with copyright law. It addresses the basics of copyright law and the exclusive rights of the copyright owner, the major exemptions used by cultural heritage institutions, and stresses the importance of "risk assessment" when conducting any digitization project. Case studies on digitizing oral histories and student work are also included.